(untitled) (Basel Institute on Governance Working Papers, 2023)
This Working Paper presents international case studies of legal frameworks addressing conflicts of interest and highlights common challenges, opportunities and lessons for practitioners and other interested stakeholders. The report covers three contexts: two national (South Korea, Brazil) and one supranational (the European Union). The analysis is based on the international standards in the 2020 guide Preventing and Managing Conflicts of Interest in the Public Sector, produced by the World Bank Group, OECD and UNODC at the request of the G20 Anticorruption Working Group. The Working Paper is published in the context of the USAID Indonesia Integrity Initiative (INTEGRITAS) project, which supports the Government of Indonesia in preventing corruption via enhancing civic engagement and strengthening integrity in the public and private sectors. The case studies and analysis will be of value to anyone interested in drafting, revising or monitoring conflict of interest legislation in any context.